Acute kidney injury following neonatal sepsis: A case report in a Cameroonian setting - Andreas Chiabi; Kate Kan; Alex Mambap; Christina Ntui; Sankara Nykam; Sandrine Ngeh; Cecilia Fomenky; Denis Nsame (Elsevier, 2024)
Neonatal sepsis is a frequent disease affecting newborns worldwide. It can be life threatening causing multi-organ dysfunction. We present a case of a 28-day old neonate who was admitted for an acute kidney injury in the context of neonatal sepsis. Management was conservative and successful, and consisted of adequately treating the infection with antibiotics, correcting electrolyte imbalances, and judiciously administrating fluids.